The Effects of Vertical Transmission on the Spread of HIV/AIDS in the Presence of Treatment - Moatlhodi Kgosimore; Edward M. Lungu (Mathematical Biosciences and Engineering)
In this study, we develop a model that incorporates treatment ofboth juveniles who were infected with HIV/AIDS through verticaltransmission and HIV/AIDS-infected adults. We derive conditionsunder which the burden of HIV/AIDS can be reduced in the populationboth in the absence of and in the presence of vertical transmission.We have determined the critical threshold parameter ($R_v^*$), whichrepresents the demographic replacement of infectives throughvertical transmission, below which treated infected juveniles canreach adulthood without causing an epidemic. Five countries insub-Saharan Africa are used to illustrate our results. We haveconcluded that $R_v^*$ is dependent on the current prevalence ratebut that a significant proportion of infected juveniles receivingtreatment can reach adulthood without causing an epidemic.